WhiA, a Protein of Unknown Function Conserved among Gram-Positive Bacteria, Is Essential for Sporulation in Streptomyces coelicolor A3(2) - Aínsa, J. A. (American Society for Microbiology, 2000)
The whiA sporulation gene of Streptomyces coelicolor A3(2), which plays a key role in switching aerial hyphae away from continued extension growth and toward sporulation septation, was cloned by complementation of whiA mutants. DNA sequencing of the wild-type allele and five whiA mutations verified that whiA is a gene encoding a protein with homologues in all gram-positive bacteria whose genome sequence is known, whether of high or low G+C content. No function has been attributed to any of these WhiA-like proteins. In most cases, as in S. coelicolor, the whiA-like gene is downstream of other conserved genes in an operon-like cluster. Phenotypic analysis of a constructed disruption mutant confirmed that whiA is essential for sporulation. whiA is transcribed from at least two promoters, the most downstream of which is located within the preceding gene and is strongly up-regulated when colonies are undergoing sporulation. The up-regulation depends on a functional whiA gene, suggesting positive autoregulation, although it is not known whether this is direct or indirect. Unlike the promoters of some other sporulation-regulatory genes, the whiA promoter does not depend on the sporulation-specific ς factor encoded by whiG.